A self-regulation model of leader authenticity based on mindful self-regulated attention and political skill. (April 2021) - Dietl, Erik; Reb, Jochen
Despite much research on leader authenticity, its antecedents remain poorly understood. We develop a self-regulatory model of leader authenticity. The model explains how both mindful self-regulated attention and political skill, as well as their interaction, are important for leaders to be authentic, and ultimately effective. Mindful self-regulated attention—a core dimension of mindfulness defined as sustained attention centered on the present moment—helps leaders stay connected to their core self amid the busyness of their (work) lives, allowing leaders to feel authentic. And, particularly in combination with political skill—a social effectiveness construct—it helps leaders interact with their employees in a way that is experienced as authentic and effective. In an experimental study (Study 1), we found that leaders who mindfully self-regulate their attention feel more authentic. In a two-wave multi-source field study (Study 2), we found that leader self-regulated attention was positively associated with employee perceptions of leader authenticity and effectiveness. Further, this relation was stronger when leader political skill was high. We discuss theoretical and practical implications of this research.